1995
DOI: 10.1128/mcb.15.5.2772
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Virus Propagation Depends Critically on Free 60S Ribosomal Subunit Concentration

Abstract: Over 30 MAK (maintenance of killer) genes are necessary for propagation of the killer toxin-encoding M 1 satellite double-stranded RNA of the L-A virus. Sequence analysis revealed that MAK7 is RPL4A, one of the two genes encoding ribosomal protein L4 of the 60S subunit. We further found that mutants with mutations in 18 MAK genes (including mak1 [top1], mak7 [rpl4A], mak8 [rpl3], mak11, and mak16) had decreased free 60S subunits. Mutants with another three mak mutations had half-mer polysomes, indicative of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
124
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(132 citation statements)
references
References 61 publications
7
124
1
Order By: Relevance
“…Deletion of either RPL8A or RPL8B had a detectable growth defect ( Fig. 1A; Yon et al 1991;Ohtake and Wickner 1995). Previously, Robledo et al (2008) showed that knockdown of human L7 led to a decrease in 60S subunits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deletion of either RPL8A or RPL8B had a detectable growth defect ( Fig. 1A; Yon et al 1991;Ohtake and Wickner 1995). Previously, Robledo et al (2008) showed that knockdown of human L7 led to a decrease in 60S subunits.…”
Section: Resultsmentioning
confidence: 99%
“…As is the case for many r-proteins (Mager et al 1997), both L7 and L8 are encoded by two different, unlinked genes (Arevalo and Warner 1990;Yon et al 1991;Ohtake and Wickner 1995). Therefore, we began by deleting each copy of the RPL7 and RPL8 genes to determine which deletion of each pair had the stronger phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, some, but not all, mutations that reduce ribosomal subunit levels reduce the expression of poly(A) Ϫ yeast viral mRNAs (44). In both cases, 60 S subunit changes produced a more pronounced effect, possibly reflecting a more critical role of the 60 S subunit joining step in enhancing translation of poly(A) ϩ mRNAs.…”
Section: Deletion Of the Small Subunit Ribosomal Protein Gene Rps51amentioning
confidence: 99%
“…The killer phenotype is caused by infection of yeast cells by the endogenous L-A and M 1 dsRNA viruses (reviewed in Wickner 1996). The M 1 virus, and hence the killer phenotype, is highly susceptible to defects in the translational apparatus, e.g., to defects in 60S ribosomal subunit biogenesis (Ohtake and Wickner 1995b), to the presence of translational inhibitors (Sommer and Wickner 1982;Carroll and Wickner 1995), to mutations in ribosomal proteins Carroll and Wickner 1995;Ohtake and Wickner 1995a;Meskauskas and Dinman 2001), and to changes in the efficiency of programmed −1 ribosomal frameshifting (−1 PRF; Dinman and Wickner 1992). In order to minimize recombination and select cells containing only mutant forms of 5S rRNA, a rigorous selection scheme involving negative selection for both the wild-type RDN1 gene and the plasmid on which it was encoded was devised (see Materials and methods).…”
Section: Generation and Characterization Of 5s Rrna Mutants In The Abmentioning
confidence: 99%